Role of Ginger Ethanolic Extract in Improving Renal Dysfunction –Induced by Gentamicin - Salma Jameel Askar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: The present study was designed to evaluate the effect of ethanolic extract of ginger rhizomein improving renal dysfunction experimentally induced by gentamicin in male rats in order to give anexperimental evidence for its established use. Duration: September 2020- December 2020. Design: In thisstudy (25) Swiss albino male rats were used weighing (200-230) gm. which were divided randomly intofive equal groups, (5) rats in each group as follows: G1 (control) which was received distilled water orallydaily for 10 days. G2: received therapeutic dose of gentamicin sulphate (5mg/kg) intramuscularly oncedaily for 10 days. G3: received two fold dose of gentamicin (10mg/kg) intramuscularly once daily for 10days. G4: received co-administration of gentamicin (5mg/kg) intramuscularly + ethanolic extract of gingerrhizome (250 mg/kg) orally daily for 10 days, while the G5: received gentamicin (10mg/kg) + ethanolicextract of ginger rhizome (250mg/kg) orally daily for 10 days. All the treatments were given in amountslevels of (0.1/100gm) B.W. Animals from each group were sacrificed at the end of 10 days and blood werecollected and sera were separated for biochemical testes , while the kidneys removed for histopathologicalexaminations . The findings: Significant increase (P<0.05) in the serum levels of uric acid, creatinineand blood urea nitrogen (BUN) in (G2&G3) as compared to (G1) group , while there were significantdecrease (P<0.05) in serum levels of these testes in the groups (G4&G5) as compared to ( G2&G3 ) groupsbeside normalizing the kidney histopathological architecture . Conclusion: It can be concluded that the coadministration of gentamicin along with ginger rhizome ethanolic extract has been exhibited more activityin improving renal dysfunctions .